Immobilization of Styrene‐Substituted 1, 3, 4‐Oxadiazoles into Thermoreversible Luminescent Organogels and Their Unexpected Photocatalyzed Rearrangement. Issue 4 (30th November 2012) - Dumur, Frédéric; Contal, Emmanuel; Wantz, Guillaume; Phan, Trang N. T.; Bertin, Denis; Gigmes, Didier
Abstract A series of styrene‐substituted 1, 3, 4‐oxadiazoles has been designed and investigated as new low‐molecular‐weight organogelators. The photophysical properties of the resulting thermoreversible organogels have been characterized by UV/Vis absorption and luminescence spectroscopies. Surprisingly, the gelation ability of the oxadiazoles depended on the presence of the styrene moiety as gelation of the investigated oxadiazoles did not take place in its absence. Gel formation was accompanied by a modification of the fluorescence of the organogelators in the supramolecular state. UV irradiation of the gels caused a rearrangement of the immobilized 1, 3, 4‐oxadiazoles bearing a styrene moiety by a tandem [4+2] and [3+2] cascade reaction. Structure modification and color change of the gels were also evident upon irradiation.